(3CReI GdJYdje GdOjfj aj GdYGde GdESdGejs - (3GdUeOj, NGddOs ((3HjQhJs (3OGQ GdacQ GdeYGUQs, 2007)
(3Ef eWdH EUdGM GdJYdje GJdOjfj djS OYhI LOjOI, Hd Efg XgQ eY eWGdY GdbQf GdYTQjf eUGMHkG HMQcI GdEUdGM(B. (3jJfGhd GdcJGH gPG GdehVhY aj bSejf deDdajf GKfjf, GdChd OQS GdeXGgQ GdCSGSjI ddCReI, aMGhd JMOjO GdeaGgje GdJj HfjJ YdjgG, Ke OQT fTCI GdHMK GdJQHhj aj GdYdhe GdTQYjI, hcjajI GdJYGed eY GdefGgL GdJYdjejI(B.. (3hCgOGa(B.. (3hYdGbI GdfU HGdJGQjN dHfGA GdeYQaI GdOjfjI, aj eMGhdI ddhUhd Edi Jchjf GdeMJhi GdJYdjej(B. (3hYGdL gPG GdbSe ETcGdGJ GdJOQjS hWQbg hhSGFdg, hJSGAd(B: (3deGPG jchf GdJQcjR Ydi GdLGfH GdeYQaj dG Ydi Jchjf GdegGQGJ? ceG YGdL GdeTcdGJ GdfGLeI Yf EgeGd GdhSGFd GdJYdjejI hWQb GdJbhje(B. (3Ke bOe QDjI LOjOI dJWhjQ efGgL JOQjS GdYdhe GdTQYjI(B. (3hYGdL GdbSe ETcGdGJ GdJOQjS hWQbg hhSGFdg, hJSGAd(B: (3deGPG jchf GdJQcjR Ydi GdLGfH GdeYQaj dG Ydi Jchjf GdegGQGJ? ceG YGdL GdeTcdGJ GdfGLeI Yfe EgeGd GdhSGFd GdJfYdjejI hWQb GdJbhje(B. (3Ke bOe QDjI LOjOI dJWhjQ efGgL JOQjS GdYdhe GdTQYjI(B. (3hYGdL GdbSe GdKGfj ef GdcJGH CReI GdJYdje GdOjfj aj GdLGeYGJ GdESdGejI, dCfg GdeaJGM ddEUdGM GdOjfj GdeLJeYj, aGdJYdje GdOjfj GdLGeYj gh GdQGaO ddbGFejf Ydi LejY CTcGd gPG GdJYdje(B. (3hbO OYe eDda gPG GdbSe HMKg HELQGA GSJWdGY BQGA CSGJPI GdLGeYGJ hNQjLjgG aj ShQjI hGdeZQH heGdjRjI(B. (3hOQS gPG GdbSe cPdc eXGgQ CReI GdJYdje GdOjfj aj GdLGeYGJ, hYRGg Edi GdJCNQ GdeGOj hGdJbfj hGdJOghQ GdCNdGbj hGdTc aj Gdbje hGdJGQjN hZjGH GdMUGfI GdacQjI(B. (3hGYJbO GdeDda aj gPG GdbSe Cf gfGc CSHGHkG NGQLjI ddCReI PGJ YdGbI HGdJCKjQ GdSjGSj Ydi GdefGgL aj eMGhdI ddbVGA Ydi GdeDSSGJ GdJbdjOjI HYO GdGSJbdGd, hCSHGHkG OGNdjI JfHY ef GdHjFI GdNGUI ddJYdje GdOjfj, JJYdb HNUhUjJg hVNGeI eMJhGg hYebg GdJGQjNj hJfhY eLGdGJg hJNUUGJg(B. (3hddVQhQI GdHMKjI OQS eda gPG GdbSe CReI GdJYdje GdOjfj deQMdI eG bHd GdLGeYI hGdJMOjGJ GdJj jhGLggG(B. (3hNJe HGbJQGMGJ ddEUdGM(B. (3QO cd ef GdHGMKjf Ydi GdBNQ hYbH Ydjg(B.s
(3GdfhY (B: (3cJGHs
Keywords: L$1 (Benseignement du fait religieuxs; Religion education; (3JYdje GdOjfs